Peripheral Dopamine Controlled by Gut Microbes Inhibits Invariant Natural Killer T Cell-Mediated Hepatitis - Xue, Rufeng; Zhang, Huimin; Pan, Jun; Du, Zhiwei; Zhou, Wenjie; Zhang, Zhi; Tian, Zhigang; Zhou, Rongbin; Bai, Li (Frontiers in Immunology, 2018)
Neurotransmitters have been shown to regulate immune responses, and thereby are critically related to autoimmune diseases. Here we showed that depletion of dopaminergic neurons significantly promoted activation of hepatic iNKT cells and augmented concanavalin A (Con A)-induced liver injury. The suppressive effect of dopamine on iNKT cells was mediated by D1-like receptor-PKA pathway. Clearance of gut microbiota by antibiotic cocktail reduced synthesis of dopamine in intestines and exacerbated liver damage, and that could be restored by recovery of gut microbiota or replenishment of D1-like receptor agonist. Our results demonstrate that peripheral dopamine controlled by gut microbes inhibits IL4 and IFNγ production in iNKT cells and suppresses iNKT cell-mediated hepatitis. Together, we propose a gut microbe-nervous system-immune system regulatory axis in modulating autoimmune hepatitis.